Non-ST Elevation Myocardial Infraction after High Dose Intravenous Immunoglobulin Infusion - Meir Mizrahi; Tomer Adar; Efrat Orenbuch-Harroch; Yair Elitzur (Case Reports in Medicine)
Intravenous immunoglobulins (IVIgs) are used for several indications, including autoimmune conditions. IVIg treatment is associated with several possible adverse reactions including induction of a hypercoagulable state. We report a 76-year-old woman treated with IVIg for myasthenia gravis, which developed chest pain and weakness following IVIg infusion. The symptoms were associated with ST segment depression in V4–6 and elevated troponin levels. The patient was diagnosed with non-ST elevation myocardial infarction (NSTEMI). The patient had no significant risk factor besides age and a cardiac perfusion scan was interpreted as normal (the patient refused to undergo cardiac catheterization). This case is compatible with IVIg-induced hypercoagulability resulting in NSTEMI. Cardiac evaluation should therefore be considered prior to initiation of IVIg treatment especially in patients with multiple cardiovascular risks.